The relative age effect and success in German elite U-17 soccer teams - Augste, C.; Lames, M. (Journal of Sports Sciences, 2011)
The aim of the study was to determine whether there is empirical evidence for advantages in performance of soccer teams because of their relative age. The practice of selecting youth players according to their momentary performance leads to relative age effects, which in turn lead to inefficient talent selection. We used the median of the birth dates as a measure of the effect size of the relative age effect and the Kolmogorov-Smirnov test to assess its significance. For the 2008-2009 season, birth dates in the three German U-17 first leagues for soccer were examined (911 players). More than half of the 41 teams differed significantly from the distribution of the corresponding German cohort. There was a significant correlation between the relative age effect and success defined by teams' final rankings (Spearman's ? = 0.328, P = 0.036). Regression analyses revealed that with a median of birth dates one month earlier the team is expected to finish 1.035 ranks better. Accordingly, selecting early born athletes is an important aspect of success in youth soccer. However, teams with no relative age effect are able to compete in the league, having the benefit to promote players with a better perspective for long and successful careers at an adult age.